International Variation in Regulations Related to Initial Coin Offerings: Preliminary Findings and A Research Agenda - Nir Kshetri (International Telecommunications Society (ITS), 2022)
As prior researchers have suggested a firm's success in an international market depends on how well its strategy fits with the nonmarket environment such as formal institutions. This paper examines the determinants of formal institutions around new areas of economic activities. Specifically, we propose a framework for understanding how the quality of formal institutions to promote entrepreneurship drives the focus of such institutions with respect to initial coin offering (ICO), which is emerging as a popular fundraising method. The paper also analyzes how nonmarket factors such as a jurisdiction's tax haven nature, regulators' perceptions of ICOs as threats to national or political interests and trade and industry associations might moderate the relations between quality of institutions and the focus of such institutions with respect to ICOs. We utilize inductive analysis. A key finding of this study is that an economy's quality of entrepreneurship-related institutions, perceived threats to national/political interests and tax haven nature lead to different policy orientations. Consequently, regulators assign different importance to promote crypto-entrepreneurship and to deal with associated risks. Regulators with main focus on promoting crypto-ventures have taken measures to enrich blockchain ecosystem and provided tax and non-tax incentives to attract such ventures. Regulators with main focus on dealing with risks of crypto-ventures are relying on regulatory sandbox and close regulatory monitoring of such ventures.
Keywords: 330; blockchain; crypto-currencies; crypto-ventures; initial coin offerings; regulatory sandboxes; tax havens